Hospital menu interventions: a systematic review of research. Issue 1 (8th February 2016) - Ottrey, Ella; Porter, Judi
Abstract : Purpose: – Most patients in developed countries solely depend on the hospital menu to order their food. The provision of menu choices to patients differs between facilities. The purpose of this paper is to determine which strategies that provide menu choices to patients are effective in improving clinical and non-clinical outcomes in hospital. Design/methodology/approach: – Five databases were searched to identify relevant publications. Prospective research published in English with the menu as the primary intervention was included. Study eligibility was determined and risk of bias assessed. Outcome data were combined narratively due to absence of homogeneous study design and outcomes. Findings: – Of the 2, 201 records screened, six studies met inclusion criteria. Standardised menu formatting and the spoken menu system were found to improve meal tray accuracy. The spoken menu and computerised interactive menu selector system enhanced aspects of patient satisfaction without cost increases. Descriptive menus may increase food consumption. Branding food items was not well supported by patients. One study rated positively for study quality with the remaining five studies receiving neutral quality ratings. Research limitations/implications: – The small number of studies conducted on each intervention and the quality of the evidence made it difficult to establish a solid evidence base around providing menu choices to patients. Further research is needed on menu ordering systems, including spoken and visual menus, to determine their impact on outcomes in hospital. Originality/value: – This review is first to examine the effectiveness of menu interventions in hospital. Hospital foodservice departments should consider these findings when reviewing local systems.